Social corporations under the spotlight: A governance perspective - Serres, Coline; Hudon, Marek; Maon, François (Journal of Business Venturing, 2022)
A series of new legal statutes for profit-seeking social ventures has emerged across geographic and institutional settings. Extant studies commonly do not make a clear distinction between these ventures. Such confusion leads to blurriness in research design and methodology, thereby limiting the relevance of findings. Moreover, researchers, entrepreneurs, and policymakers often lack a clear view of the unique organizational and governance aptitudes these ventures call for, to sustain and grow over time. Thus, this study has two objectives: (1) to clarify the panorama of novel companies that legally commit themselves to a social mission, gathered under the term “social corporation,” by providing a comprehensive typology of these organizations and (2) to identify the governance capabilities that social corporations develop to be sustainable and avoid mission drift in the long run. Our analysis of corporate-governing documents leads us to classify social corporations into three types: hard-law, soft-law, and bylaw. In addition to this typology, our multiple case study uncovers five key governance capabilities of social corporations related to performance, conformance, and responsibility—the main pillars of organizational governance. Overall, our work contributes to a better understanding of novel forms of social entrepreneurship emerging on the market. More important, it casts light on the governance processes that characterize them.